2011
DOI: 10.1089/aid.2010.0118
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of HIV Type 1 BF Recombinant Sequences from South America Dates the Origin of CRF12_BF to a Recombination Event in the 1970s

Abstract: HIV-1 epidemics in South America are believed to have originated in part from the subtype B epidemic initiated in the Caribbean/North America region. However, circulation of BF recombinants in similar proportions was extensively reported. Information currently shows that many BF recombinants share a recombination structure similar to that found in the CRF12_BF. In the present study, analyzing a set of 405 HIV sequences, we identified the most likely origin of the BF epidemic in an early event of recombination.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 47 publications
4
11
0
Order By: Relevance
“…In the six data sets of the pure pol and env genes (Figs. 4 and 5), these two sequences clustered together in the trees, reinforcing the monophyletic origin proposed by Dilernia et al 30 . However, more than one recombination event between subtypes B and F1 must have occurred, since several strains could be considered as URF_B/F1.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In the six data sets of the pure pol and env genes (Figs. 4 and 5), these two sequences clustered together in the trees, reinforcing the monophyletic origin proposed by Dilernia et al 30 . However, more than one recombination event between subtypes B and F1 must have occurred, since several strains could be considered as URF_B/F1.…”
Section: Discussionsupporting
confidence: 82%
“…Regarding the epidemic of subtypes C, B, F1 and recombinants B/F1 in South America 28,29,30,31 , most studies stated the need of analyzing sequences of "pure" subtypes to determine if introductions in different countries occurred once or multiple times from different geographic origins. Following these recommendations, we divided the sequences of the pol and env genes into "pure" data sets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, several studies [Aulicino et al, 2007;Bello et al, 2010;Dilernia et al, 2011] have reported recently that the origin of the HIV-BF subtype in South America dates from the beginning of the 1970s, overlapping with the HPD 95% found for the HCV-1a Argentinean sequences included into the cluster M. Nevertheless, the 95% HPD intervals found for the tMRCA of the HCV-1a cluster, final conclusions remain elusive. This limitation deserves further investigation with a longer time span of sampling that allows reaching short confidence intervals for dates, and higher precision.…”
Section: Discussionmentioning
confidence: 98%
“…Reverse transcription was performed with MMLV reverse transcriptase (Promega, Madison, WI) and random hexamers (Promega). The HCV-E2, HCV-NS5A and HIV-pol nested-PCR protocols were performed as described previously [Bolcic et al, 2008a;Dilernia et al, 2011] thus obtaining HCV-E2, HCV-NS5A, and HIV-pol amplicons with lengths of 321 bp (positions 2211-2531), 405 bp (positions 6918-7322), and 1,060 bp (positions 2253-3315) nucleotides, respectively. The products amplified were electrophoresed on 1.5% agarose gel and visualized by ethidium bromide staining.…”
Section: Patientsmentioning
confidence: 99%